Grants Versus Loans - Ulku, Hulya (IMF Working Papers; Working Paper ;, 2004)
Under what conditions should grants be preferred to loans? To answer this question, we present a simple model a la Krugman (1988) and show that, for any given level of developmental assistance, the optimal degree of loan concessionality is positively associated with economic growth if countries are poor, have bad policies, and high debt obligations. We then test our model by estimating a modified growth model for a panel of developing countries, and find evidence supporting our predictions. Finally, we assess the determinants of current aid allocations and find that the degree of concessionality is negatively correlated with countries' levels of development.